RANCANG BANGUN PROTOTYPE ALAT PENDETEKSI DAN PENCEGAHAN KEBAKARAN DI TEMPAT PENYIMPANAN BAHAN BAKU PT IKPP SERANG - Mujiburohman Mujiburohman; Khasan Asrori; Muhamad Zakaria (LPPM Unbaja, 2025)
Supervision at the storage of raw materials of PT Indah Kiat Pulp & Paper (IKPP) Serang carried out by the safety team directly and from CCTV monitoring is still not effective against fires because there is no fire detection device in the area, and for fire prevention in the place there is a sprinkler that is used to control the temperature by watering water based on the time not based on the actual temperature in the field, as well as when a fire occurs in the place reporting and watering Sprinkle still uses human labor. The research method used is the SDLC (Software Development Life Cycle) model with the Waterfall approach, which includes requirements analysis, system design with the integration of temperature sensors and fire sensors on Arduino devices, system implementation, functionality testing, and routine maintenance. The purpose of this research is to design a fire detection system that can provide early detection of fire spots, fire prevention by controlling the temperature of raw materials with automatic watering tools, as well as being able to run automatic watering and provide notifications directly to the security team through WhatsApp Gateway when a fire occurs. The results of the study show that the system developed can provide effective monitoring of environmental temperature and detect fires, which has the potential to reduce the risk of loss and improve response to emergency events in the industrial environment of IKPP Serang.